Analisis Faktor-Faktor yang Mempengaruhi Penilaian KinerjaSatuan Kerja Perangkat Daerah Di Kota Bandung - Yuliana Gunawan; Aurora Angela; Ilham Pranata (Universitas Kristen Maranatha, 2018)
The purpose of this research is to reveal other factors that may affect the performance of SKPD in Indonesia. Factors used are incentive-oriented performance appraisal system, exploration-oriented performance appraisal system with contractibility as a moderating variable. This research was done in 3 SKPD located in Bandung City. Moderated Regression Analysis (MRA) have been used to analyzed the hypothesis. The results showed that incentive-oriented performance appraisal system and exploration-oriented performance appraisal system had no effect on SKPD performance, and when moderated by contractibility variable, the result also had no effect on SKPD performance.Â Keywords:Incentive-oriented Performance Appraisal System, Performance-oriented Appraisal Performance System, Contractibility, SKPD Performance.Â